The Role of Proprioception in the Sagittal Setting of Anticipatory Postural Adjustments During Gait Initiation - Pereira, Marcelo P. [UNESP]; Pelicioni, Paulo H. Silva [UNESP]; Gobbi, Lilian T.B. [UNESP] (My University, 2015)
Purpose. Previous studies have studied the role of proprioception on the setting of anticipatory postural adjustments (APA) during gait initiation. However, these studies did not investigate the role of proprioception in the sagittal APA setting. We aimed to investigate the role of proprioception manipulation to induce APA sagittal adaptations on gait initiation. Methods. Fourteen healthy adults performed gait initiation without, and with, vibration applied before movement onset, and during movement. In addition, the effects of two different vibration frequencies (80 and 120Hz) were tested. Vibration was applied bilaterally on the tibialis anterior, rectus femoris and trapezius superior. The first step characteristics, ground reaction forces and CoP behaviour were assessed. Results. Vibration improved gait initiation performance regardless of the moment it was applied. CoP velocity during the initial phase of APA was increased by vibration only when it was applied before movement. When vibration was applied to disturb the movement, no effects on the CoP behaviour were observed. Manipulation of vibration frequency had no effects. Conclusions. Rather than proprioception manipulation, the results suggest that post-vibratory effects and attentional mechanisms were responsible for our results. Taken together, the results show that sagittal APA setting is robust to proprioception manipulation.
Keywords: anticipatory postural adjustment; gait initiation; proprioception; vibration